THE EFFECT OF BREATHING EXERCISES ON STRESS, ANXIETY, AND DEPRESSION IN ADOLESCENTS - Tresnaya Zhafirah Widanti; Indah Munajatin Amalia; Intan Munawaroh (Ikatan Dosen Menulis, 2025)
This study aims to determine the effect of breathing exercises on stress, anxiety, and depression levels among adolescents. The method used was quantitative with a one-group pretest-posttest design. The sample consisted of five adolescent participants aged 15–19 years, selected using purposive sampling based on specific inclusion criteria. The intervention involved diaphragmatic breathing exercises conducted twice daily over seven consecutive days. The research instrument used was the Depression Anxiety Stress Scale (DASS-21), administered before and after the intervention. In addition, participants were asked to write daily reflections regarding their experiences during the breathing sessions. The results showed a decrease in depression and anxiety scores among some participants, especially those with moderate to severe symptoms who practiced consistently. Conversely, stress scores tended to increase in participants who were less consistent. The conclusion of this study is that breathing exercises can serve as a simple intervention with positive impacts on adolescent mental health, particularly in reducing depressive symptoms. It is recommended that breathing practices be incorporated into school-based mental health promotion programs. This study contributes to the growing body of non-pharmacological approaches utilizing breath regulation to enhance adolescent psychological well-being.